Presence of porcine circovirus type 2 in porcine herds of Baja California, Mexico - Gómez Gómez, Sergio Daniel (2020)
The aim of this study was to detect the presence of porcine circovirus type 2 (PCV2) in pig herds of Baja California, Mexico, using the polymerase chain reaction (PCR) technique. Blood samples (n=97) were collected from 97 pigs in 26 farms. The DNA was extracted from the buffy coat and the samples were grouped into 19 groups of five samples and one of two samples for PCR analysis. Specific primers were used to amplify a PCV2 ORF2 fragment of 264 base pairs and using a commercial vaccine as a positive control. The viral fragment was detected in 15% (3/20) of the groups. This is the first report in which the presence of porcine circovirus type 2 in Baja California is evidenced.